3D local atomic structure evolution in a solidifying Al-0.4Sc dilute alloy melt revealed in operando by synchrotron X-ray total scattering and modelling. (1st April 2022) - Huang, Shi; Luo, Shifeng; Qin, Ling; Shu, Da; Sun, Baode; Lunt, Alexander J G; Korsunsky, Alexander M; Mi, Jiawei
Abstract: Using synchrotron X-ray total scattering and empirical potential structure refinement modelling, we studied systematically in operando condition the disorder-to-order local atomic structure transition in a pure Al and a dilute Al-0.4Sc alloy melt in the temperature range from 690 °C to 657 °C. In the liquid state, icosahedral short-range ordered Sc -centred Al polyhedrons form and most of them with Al coordination number of 10–12. As the melt is cooled to the semisolid state, the most Sc -centred polyhedrons become more connected atom clusters via vertex, edge and face-sharing. These polyhedrons exhibit partially icosahedral and partially face-centred-cubic symmetry. The medium-range ordered Sc -centred clusters with face-sharing are proved to be the "precursors" of the L12 Al3 Sc primary phases in the liquid-solid coexisting state. Graphical abstract: Image, graphical abstract